Incidencia de la actividad pesquera en la tasa de mortalidad de otaria flavescens en el área nacional de recreación Playas de Villamil - Córdova Hernández, Vanessa Margoth (2021)
The increasing use of coastal waters for fishing activities has increased the interaction of sea lions and fishermen, which in turn influences the death of this species. The objective was to evaluate the incidence of fishing activity and the total population in the mortality rate of Otaria flavescens in the Playas Villamil National Recreation Area, through a non-experimental investigation, an observation sheet was applied for a month and a survey was applied to 250 fishermen. It was verified that 3 types of fishing are carried out (artisanal, mixed and industrial); 14 km of beach were covered, corresponding to the entire coastal profile of the protected area, geo-referencing the points where the stranding was evidenced. The mortality rate was established by the method proposed by the Economic Commission for Latin America and the Caribbean and the review of the database of the Playas Villamil National Recreation Area, which was classified by the type of activity; For artisanal fishing a rate of 75.18% was obtained for mixed fishing the rate was 21.69% while for industrial fishing the total mortality was 3.12% during the study period. Regarding the relationship of the incidence of fishing activities on the mortality rate of Otaria flavescens; A very high positive linear correlation of 0.95 was found, that is to say that the larger the population, the greater the number of deaths of the sea lions.